Type 2 diabetes mellitus and the cardiometabolic syndrome: impact of incretin-based therapies - Schwartz S (Dove Medical Press, 2010)
Stanley Schwartz1, Benjamin A Kohl21Department of Endocrinology, Diabetes, and Metabolism, University of Pennsylvania, Philadelphia, Pennsylvania, USA; 2Department of Anesthesiology and Critical Care, School of Medicine, University of Pennsylvania, Philadelphia, Pennsylvania, USAAbstract: The rates of type 2 diabetes mellitus, obesity, and cardiovascular disease (CVD) continue to increase at epidemic proportions. It has become clear that these disease states are not independent but are frequently interrelated. By addressing conditions such as obesity, insulin resistance, stress hyperglycemia, impaired glucose tolerance, and diabetes mellitus, with its micro- and macrovascular complications, a specific treatment strategy can be developed. These conditions can be addressed by early identification of patients at high risk for type 2 diabetes, prompt and aggressive treatment of their hyperglycemia, recognition of the pleiotropic and synergistic benefits of certain antidiabetes agents on CVD, and thus, avoiding potential complications including hypoglycemia and weight gain. Incretin-based therapies, which include glucagon-like peptide-1 (GLP-1) receptor agonists and dipeptidyl peptidase-IV (DPP-IV) inhibitors, have the potential to alter the course of type 2 diabetes and associated CVD complications. Advantages of these therapies include glucose-dependent enhancement of insulin secretion, infrequent instances of hypoglycemia, weight loss with GLP-1 receptor agonists, weight maintenance with DPP-IV inhibitors, decreased blood pressure, improvements in dyslipidemia, and potential beneficial effects on CV function.Keywords: cardiovascular disease, glucose control, GLP-1 receptor agonists, DPP-IV inhibitors